Origin of Open‐Circuit Voltage Enhancements in Planar Perovskite Solar Cells Induced by Addition of Bulky Organic Cations. (12th December 2019) - Lin, Chieh‐Ting; Lee, Jinho; Kim, Jinhyun; Macdonald, Thomas J.; Ngiam, Jonathan; Xu, Bob; Daboczi, Matyas; Xu, Weidong; Pont, Sebastian; Park, Byoungwook; Kang, Hongkyu; Kim, Ji‐Seon; et al.
Abstract: The origin of performance enhancements in p‐i‐n perovskite solar cells (PSCs) when incorporating low concentrations of the bulky cation 1‐naphthylmethylamine (NMA) are discussed. A 0.25 vol % addition of NMA increases the open circuit voltage ( V oc ) of methylammonium lead iodide (MAPbI3 ) PSCs from 1.06 to 1.16 V and their power conversion efficiency (PCE) from 18.7% to 20.1%. X‐ray photoelectron spectroscopy and low energy ion scattering data show NMA is located at grain surfaces, not the bulk. Scanning electron microscopy shows combining NMA addition with solvent assisted annealing creates large grains that span the active layer. Steady state and transient photoluminescence data show NMA suppresses non‐radiative recombination resulting from charge trapping, consistent with passivation of grain surfaces. Increasing the NMA concentration reduces device short‐circuit current density and PCE, also suppressing photoluminescence quenching at charge transport layers. Both V oc and PCE enhancements are observed when bulky cations (phenyl(ethyl/methyl)ammonium) are incorporated, but not smaller cations (Cs/MA)—indicating size is a key parameter. Finally, it demonstrates that NMA also enhances mixed iodide/bromide wide bandgap PSCs ( V oc of 1.22 V with a 1.68 eV bandgap). The results demonstrate a facile approach to maximizing V oc and provide insights into morphological control and charge carrier dynamics induced by bulky cations in PSCs. Abstract : Bulky cation addition to perovskite solar cells is demonstrated as an effective means of significantly improving device performance. Detailed structural characterization reveal additives are located at surfaces and grain boundaries, resulting in suppression of nonradiative recombination. Judicious cation selection results in MAPI‐based perovskite cells with a power conversion efficiency >20% and MAPBrI cells with a V oc of 1.22 V.